Double-echo gradient chemical shift MR imaging fails to differentiate minimal fat renal angiomyolipomas from other homogeneous solid renal tumors. Issue 3 (March 2015) - Ferré, R.; Cornelis, F.; Verkarre, V.; Eiss, D.; Correas, J.M.; Grenier, N.; Hélénon, O.
Highlights: Diagnosis of AMLs with minimal fat (mfAMLs) is still challenging with MRI. Drop of signal on opposed-phase MR imaging is not specific of mfAMLs. Double-echo gradient-echo sequences cannot accurately differentiate renal mfAMLs from other renal tumors. Abstract: Objectives: The purpose of this retrospective study was to evaluate the diagnostic performance of double-echo gradient chemical shift (GRE) magnetic resonance (MR) imaging for the differentiation of angiomyolipomas with minimal fat (mfAML) from other homogeneous solid renal tumors. Methods: Between 2005 and 2010 in two institutions, all histologically proven homogenous solid renal tumors imaged with computed tomography and MR imaging, including GRE sequences, have been retrospectively selected. A total of 118 patients (mean age: 61 years; range: 20–87) with 119 tumors were included. Two readers measured independently the signal intensity (SI) on GRE images and calculated SI index (SII) and tumor-to-spleen ratio (TSR) on in-phase and opposed-phase images. Intra- and interreader agreement was obtained. Cut-off values were derived from the receiver operating characteristic (ROC) curve analysis. Results: Twelve mfAMLs in 11 patients were identified (mean size: 2.8 cm; range: 1.2–3.5), and 107 non-AML tumors (3.2 cm; 1–7.8) in 107 patients. The intraobserver reproducibility of SII and TSR was excellent with an intraclass correlation coefficient equal to 0.99 [0.98–0.99]. The coefficient of correlation between the readers was 0.99. The mean values of TSR for mfAMLs and non-mfAMLs were −7.0 ± 22.8 versus −8.2 ± 21.2 for reader 1 and −6.7 ± 22.8 versus −8.4 ± 20.9 for reader 2 respectively. No significant difference was noticed between the two groups for SII ( p  = 0.98) and TSR ( p  = 0.86). Only 1 out of 12 mfAMLs and 11 of 107 non-AML tumors presented with a TSR inferior to −30% ( p  = 0.83). Conclusion: In a routine practice, GRE sequences cannot be a confident tool to differentiate renal mfAMLs from other homogeneous solid renal tumors.